Reliability Engineering Theory and Practice - Birolini, Alessandro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book shows how to build in, evaluate, and demonstrate reliability & availability of components, equipment, systems. It presents the state-of-the-art of reliability engineering, both in theory and practice, and is based on the author's 30 years experience in this field, half in industry and half as Professor of Reliability Engineering at the ETH, Zurich. The structure of the book allows rapid access to practical results. Besides extensions to cost models and approximate expressions, new in this edition are investigations on common cause failures, phased-mission systems, availability demonstration and estimation, confidence limits at system level, trend tests for early failures or wearout, as well as a review of maintenance strategies, an introduction to Petri nets and dynamic FTA, and a set of problems for home-work. Methods and tools are given in a way that they can be tailored to cover different reliability requirement levels and be used for safety analysis as well. This book is a textbook establishing a link between theory and practice, with a large number of tables, figures, and examples to support the practical aspects.
Basic Concepts, Quality and Reliability Assurance of Complex Equipment and Systems -- Reliability Analysis During the Design Phase (Nonrepairable Elements up to System Failure) -- Qualification Tests for Components and Assemblies -- Maintainability Analysis -- Design Guidelines for Reliability, Maintainability, and Software Quality -- Reliability and Availability of Repairable Systems -- Statistical Quality Control & Reliability Tests -- Quality and Reliability Assurance During the Production Phase (Basic Considerations) -- Annexes.
Keywords: Engineering; System safety; Electronics; Economics; Business planning; Engineering; Quality Control, Reliability, Safety and Risk; Organization/Planning.; R & D/Technology Policy; Electronics and Microelectronics, Instrumentation